Analysis Of Village Fund Management In West Kosio Village, Bolaang Mongondow District - Destrina Maria; Hendrik Gamaliel; Claudia WM korompis (ACCOUNTABILITY, 2024)
Village Funds are funds sourced from the State Revenue and Expenditure Budget which are intended for villages to finance government administration, implementation of development, community development and the community. The aim of this research is to analyze and find out how the village fund management process is in West Kosio Village, Dumoga Tengah District, Bolaang Mongondow Regency in terms of elements of village fund management based on Ministry of Home Affairs Regulation Number 20 of 2018. The type of research method used is qualitative research with a descriptive approach. The results of this research show that the planning, implementation, reporting and accountability stages have basically been implemented in accordance with Permendagri No. 20 of 2018, however there are only a few things that need to be considered at the further planning stage. At the reporting stage there was a delay in synchronizing the accountability report and the APBDes realization report and the accountability stage where the APBDES realization report could not be included on the West Kosio Village website. Keywords:Analysis, Village Fund management